Optimizing Charge and Discharge of Lithium-Ion Batteries by Deploying PID Controller with Coupled Electro-Thermal-Aging Dynamic - Hudaya, Chairul; Akbar, Iwan Bahyudin; Verdianto, Ariono (International Journal of Electrical, Computer, and Biomedical Engineering, 2024)
Lithium-ion batteries (LIBs) are extensively utilized in many applications, from power plant utilities to portable electronic devices. Nevertheless, the performance and longevity of the LIB are affected by the interconnected electro-thermal-aging (ETA) dynamics that occur during the repeated process of charging and discharging. This study presents a technique for managing the charging and discharging of LIBs by controlling the operational voltage, addressing this issue. The technique involves employing a proportional-integral-derivative (PID) controller, which involves interconnected ETA dynamics. The result of the suggested technique is confirmed by comparing experimental data obtained from a cylindrical 26650 lithium-iron phosphate (LFP). The PID controller optimizes the response time of charging and discharging through the voltage while affecting the lifetime of the cell. The results indicated that the implementation of the PID controller allows for a rapid and secure charging and discharging process for LIB, leading to improved cell health and a longer cell life expectancy by controlling a certain degree of parameter known as overshoot. This strategy has the potential to be implemented in the charging and discharging process that positively affects the LIBs performance.